Pentingnya Pendidikan dan Pelatihan Pembuatan Perjanjian Kerja Bersama (PKB) pada Serikat Pekerja Seluruh Indonesia (SPSI) Kabupaten Banyumas - Sri Wahyu Handayani (Jurnal Idea Hukum, 2017)
Labor unions are workers association organizations that will fight for workers' rights when dealing with entrepreneurs. However, based on previous research, labor unions in Banyumas District experienced "death suspended". Its presence has not been felt by the members, it is supported by a survey conducted by the authors that of the 113 members of the All Indonesian Labor Union Federation (Serikat Pekerja Seluruh Indonesia) of Banyumas Regency, 90% have no Collective Labor Agreement (Perjanjian Kerja Bersama). The existence of these conditions often raises problems in the field of employment, especially labor unions. Underpinning the situation analysis is an urgent need to provide education and training of PKB for unions with partners of the All-Indonesia Labors Union Federation (SPSI) in Banyumas Regency under the supervision of Ministry of Manpower Republic Indonesia (Dinas Tenaga Kerja, Koperasi dan Unit Kredit Mikro Republik Indonesia) through community service activities, as devotion is a strategic means of transferring science and technology. Approach method of this writing is sociological juridical with the type of primary and secondary data and methods of presentation of data in the form of descriptive narrative. The purpose of this paper is to publish the results of community service in the form of education and training of PKB making in SPSI Banyumas Regency in order to be able to make PKB correct so that will guarantee the sustainability and protection for workers and support the creation of harmonious working relationship between workers and employers in Banyumas Regency.Â Keywords: Labor Unions; Collective Labor Agreement (PKB); work relationship.